Call for rethinking on fashion design education in the era of post-pandemic: insights from Turkey (Revista de Ensino em Artes, Moda e Design, 2022)
In this study, the benefits and challenges of remote education in textile and fashion design are examined. The case of the study is Department of Textile and Fashion Design, Faculty of Architecture and Design in Eskişehir Technical University, Turkey. The data is collated through many assessment meetings with academics, students, and top management held during and after the pandemic, as well as personal experiences as a manager and faculty member, plus varied unstructured interviews with academicians, undergraduates, management, and other employees. The meeting and interview notes were transcribed and analyzed by descriptive analyses. As the result, critical insights from various aspects and a SWOT analysis of remote education activities performed during the pandemic are provided.